Essays on the Macroeconomic Effect of Natural Resource Rents - (:unkn) unknown (My University, 2014)
This dissertation comprise of two chapters on the macroeconomic effect of natural resource rents. Specifically, we focus on the effect of resource rents on human capital accumulation. In chapter one, we present a new mechanism for the curse of natural resources, i.e., "why natural resource rents if distributed as transfers to individuals' income might retard economic growth and development: their effect on incentives to invest in human capital". Extending an OLG model for this purpose, we show that the windfall rents from natural resources, when transferred directly to citizens distort their incentives away from accumulating the optimum level of human capital and thus from economic growth. This increases the chance of a low-level equilibrium trap and reduces the chance of converging to a higher income per capita in the long run. In chapter two, we present a dynamic panel data model, and a cross section model to see the effect of transfers in countries with high natural resource rents per person on human capital accumulation. We use tertiary education as a human capital indicator, since at this educational level, people choose to accumulate professional skills and direct their talents to sectors with the highest expected return. Using a dynamic panel data model for five years averages of tertiary education, one can see that the combined effect of government transfers and natural resource rents per labor have a negative and significant effect on human capital. However, using a cross section analysis for the same purpose, one can see that not only the combined effect of resource rents per labor and government transfers have a negative and significant effect on tertiary education, but also resource rents per labor alone have a negative and significant effect on tertiary education. Our cross section results coincide with the natural resource curse literature as it shows that resource rents have a long-term negative effect on social capital investments such as tertiary education.
Keywords: Economic Development; Economic Growth; Human Capital; Macroeconomics; Natural Resource Rents; Natural Resources